The epidemiology and characteristics of carbon monoxide poisoning among recreational boaters. (February 2015) - LaSala, G.; McKeever, R.; Okaneku, J.; Jacobs, D.; Vearrier, D.
Abstract Introduction. Carbon monoxide (CO) poisoning has been reported in the setting of recreational boating however, previous research addressing the epidemiology of carbon monoxide-related injury and death in recreational boaters has been limited. Materials and methods. The United States Coast Guard (USCG) Recreational Boating Statistics annual reports for the 10-year period 2002 – 2011 were analyzed to determine the epidemiology and characteristics of carbon monoxide poisoning among recreational boaters in the United States. Regression analysis was performed to determine statistical significance for trend. Results. The mean number of accidents, injuries and deaths per year due to CO exposure on recreational watercrafts was 14.5 (95% CI 12.1-16.9), 30.9 (95% CI 22.4-39.4) and 6.7 (95% CI 4.5-9.0) respectively. Cabin motorboats accounted for 49 accidents, 123 injuries and 29 deaths. California had 24 carbon monoxide- related accidents over the 10-year study period. Regression analysis showed no overall linear trend in the number of carbon monoxide-related boating accidents, injuries, or deaths as an absolute number or as a percent of all boating accidents, injuries or deaths over the study period. Discussion. The majority of carbon monoxide-related boating accidents, injuries and deaths occurred with cabin motorboats. The state with the largest number of carbon monoxide-related accidents over the 10-year study period was California. Conclusions. Carbon monoxide-related accidents involving recreational boating constitute an important and under recognized cause of injury and death in the United States.